Analisis Current Ratio Pada PT Indofood Sukses Makmur, TBK - Hikmah, Nurul; Muniarty, Puji (Pascasarjana STIE Amkop Makassar, 2024)
This research aims to find out how much the Current Ratio value is at PT Indofood Sukses Makmur, Tbk. The research method used is descriptive research with a quantitative approach. The sample for this research consists of financial statements, balance sheet, profit and loss, for 10 years from the 2013-2022 period. Research sampling is purposive sampling. With research data collection techniques using documentation and literature study. The research data analysis technique is one sample t test and mean to find standard deviations using Spss V.20. The research results show that the analysis of the Current Ratio value at PT Indofood, Tbk over the last 10 years with an average of 182.7% is in poor condition, which means the company is not good in its Current Ratio.Keywords: Current Ratio